TRAJECTORIES OF CHINESE-MUSLIM STUDENTS’ CULTURAL IDENTITY AND THEIR CHALLENGES IN UIN MALANG - Rosi, Rois Imron; Yousif, Ahmad F (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Understanding cultural identity among students is a critical yet often underexplored dimension of educational research, particularly in multicultural societies. This study investigates the identity formation processes of Chinese-Muslim students in Malang, Indonesia, emphasizing the urgency of fostering cultural awareness and tolerance in educational settings. The research highlights how identity construction directly influences students’ sense of belonging and participation in society. Furthermore, it underscores the importance of cultural sensitivity for educators who engage with diverse learners. Employing a qualitative methodology, this study explores the lived experiences of five Chinese-Muslim students in navigating their cultural identities. Findings reveal that all participants belong to the Hui ethnic group but tend to self-identify as